2022
DOI: 10.1038/s41746-022-00658-x
|View full text |Cite
|
Sign up to set email alerts
|

Localization-adjusted diagnostic performance and assistance effect of a computer-aided detection system for pneumothorax and consolidation

Abstract: While many deep-learning-based computer-aided detection systems (CAD) have been developed and commercialized for abnormality detection in chest radiographs (CXR), their ability to localize a target abnormality is rarely reported. Localization accuracy is important in terms of model interpretability, which is crucial in clinical settings. Moreover, diagnostic performances are likely to vary depending on thresholds which define an accurate localization. In a multi-center, stand-alone clinical trial using tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Among the 63 studies, 56 studies identified pneumothorax on chest radiography [ 26 81 ], four studies on computed tomography [ 82 85 ], one study on ECG [ 86 ], one study used chest radiography and photography using a smartphone [ 87 ], and one study used chest radiography and tabular data [ 88 ]. Six studies developed and internally tuned DLs [ 37 , 52 , 63 , 67 , 74 , 76 ], 25 studies also internally tested their DLs [ 32 , 33 , 35 , 38 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 55 , 60 , 65 , 69 , 70 , 73 , 75 , 79 83 , 85 , 86 ] and 32 studies externally tested the DLs [ 26 31 , 34 , 36 , 39 , 42 , 44 , 46 , 49 , 51 , 53 , 54 , 56 59 , 61 , 62 , 64 , 66 , 68 , 71 , 72 , 77 , 78 , 84 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 63 studies, 56 studies identified pneumothorax on chest radiography [ 26 81 ], four studies on computed tomography [ 82 85 ], one study on ECG [ 86 ], one study used chest radiography and photography using a smartphone [ 87 ], and one study used chest radiography and tabular data [ 88 ]. Six studies developed and internally tuned DLs [ 37 , 52 , 63 , 67 , 74 , 76 ], 25 studies also internally tested their DLs [ 32 , 33 , 35 , 38 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 55 , 60 , 65 , 69 , 70 , 73 , 75 , 79 83 , 85 , 86 ] and 32 studies externally tested the DLs [ 26 31 , 34 , 36 , 39 , 42 , 44 , 46 , 49 , 51 , 53 , 54 , 56 59 , 61 , 62 , 64 , 66 , 68 , 71 , 72 , 77 , 78 , 84 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies compared the performance of DL with physicians: two studies compared DL with experts (not a resident or technologist) [ 42 , 83 ], two studies compared DL with both experts and non-experts [ 43 , 68 ] and one study compared DL with non-experts only [ 34 ]. Two studies compared the performance of DL with radiology reports written in daily clinical practice [ 42 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations